Effect of White Ginger Rhizome Extract (Zingiber officinale var. amarum) on Pregnancy in Mice (Mus musculus L.) Early Post-implantation Stage - Harlis, Wa Ode; Salwinda, Salwinda; Malik, Nurhayu; Resman, Resman (Jurnal Pijar Mipa, 2024)
White ginger (Zingiber officinale var. Amarum) contains compounds in the antifertility group, namely flavonoids, terpenoids, and essential oils (gingerol and shogaol). Flavonoids can interfere with zygote division and implantation, while terpenoids and essential oils disrupt sperm transport and cause sperm to clot in male animals. This study aims to determine the effect of white ginger (Zingiber officinale var. Amarum) rhizome extract on the mouse (Mus musculus L.) early post-implantation stage. This research type is experimental and structured using a Completely Randomized Design (CRD) pattern. A total of 16 female mice weighing 20-30 g aged 2-3 months were divided into four treatments, namely K1 (control), K2 (0.7 mg/g BW), K3 (1.4 mg/g BW), and K4 (2.8 mg/g BW) white ginger rhizome extract. The extract is given orally at 0.5 mL/head/day on the 4th to 8th day of pregnancy. The mother's body weight is weighed every three days. On the 18th day of pregnancy, mice were sacrificed using chloroform and dissected to observe early post-implantation pregnancy parameters. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's follow-up test with a confidence level of 95%.   The research showed that white ginger rhizome extract significantly reduced the percentage of implantation (IM) and the percentage of live fetuses (FH), causing fetal growth to be hampered. The rate of implantation (IM) is K1 (1.8%), K2 (0.52%), K3 (0.49%). The percentage of live fetuses (FH) was K1 (1.06%), K2 (0.48%), and K3 (0.30%), while no fetus was found in K4. K3 treatment (1.4mg/g) causes fetal growth to be hampered. White ginger rhizome extract, on average, increases post-implantation mortality (KPI) and percentage of embryo resorption (ER) and reduces fetal weight. Based on the results of this study, it is concluded that white ginger extract has antifertility properties in female animals because it causes pregnancy disorders, so it is hoped that the use of white ginger in early pregnancy will be reduced.